O Programa Nacional de Assistência Estudantil (PNAES): uma reflexão sobre sua implementação na UFPB - Mariz, Suellem Dantas (2012)
This study has aimed at examining the consequences of the National Student Assistance Program (PNAES) in assisting the student UFPB, identifying progress and / or setbacks to the realization of the right of access to and residence / university. It is chosen by the dialectical method to guide the process of research and analysis, considering the object of study proposed. Consider to be relevant bibliographic and documentary research for the study to which we propose. From our research we found that in Brazil the student assistance policy has been operationalized as other social policies, with strong repercussions of neoliberal ideology and against reform of the state - the latter is also held in the neoliberal mold - they bring in their wake criticisms regarding the design and implementation of social rights model. And consequently bring a new mode of state management, in which social rights should not be the responsibility of the state, but civil society. It was also possible in the course of our professional study and observation while the area to observe the reality of commodification of Brazilian higher education policy. It is a reality that strikes the eye and that is quite visible in various ways in our IFES. We checked several limitations to the operationalization of student assistance policy in IFES: resource constraints, professional and in many cases the lack of political will to implement it. Despite the deployment of PNAES, still can not see significant changes in student assistance UFPB. The operating conditions of the assistance programs are still quite precarious and restricted to basic, housing and food issues. Consider to be a very complex task to ensure the operationalization of Student Assistance Policy in view of enforcing rights. And the big challenge is to overcome the serious limitations that permeate this policy, which are and will still be the source of many confrontations in our day-to-day business, the struggle for concrete possibility to consolidate and extend the rights of students and consequently the higher education policy.